Pemanfaatan Limbah Kopi dan Kakao Sebagai Pupuk Kompos yang Berkualitas di Desa Karang Sidemen Kecamatan Batukliang Utara Kabupaten Lombok Tengah - Abdullah, Sirajuddin Haji; Priyati, Asih; De Side, Gagassage Nanaluih; Sumarsono, Joko; Dewi, Endang Purnama; Amaliah, Wenny; Putra, Guyup Mahardhian Dwi; Wijaya, Andre (Universitas Mataram, 2025)
Karang Sidemen Village is one of the outermost villages in Central Lombok Regency. Located at the northern tip of Mount Rinjani. As a village located at the foot of Lake Segara Anak, this village has a fertile and prosperous land contour. With the potential for large plantations and forest products, the government then designated this village as a Holtipark Village or horticultural park with various high-value plants including cocoa plants. Cocoa as a leading commodity III has not fully used technological processing and the trade value is still local. The problems that occur in Karang Sidemen Village due to abundant cocoa production with less than optimal handling of the results, in addition to the waste produced from handling its processed products, are one problem that must also be considered at the same time. An alternative solution offered for handling cocoa fruit skin waste in Karang Sidemen Village is by processing waste into compost that can be applied as organic material to increase soil fertility. By utilizing cocoa fruit skin waste as compost, it can provide cheap and environmentally friendly organic fertilizer, reduce the pile of organic waste scattered in the plantation environment, help manage waste early and quickly, reduce the need for land for disposal, and save the environment from damage and disturbances in the form of odor or air pollution. In this community service activity, the community is given socialization on how to process waste and the manufacturing process to the application of compost fertilizer utilization which can later be used as organic fertilizer to maintain, improve or increase soil fertility. With this alternative compost fertilizer, it is hoped that it can reduce the accumulation of waste produced by the community so that the cleanliness and beauty of Karang Sidemen Village as an agrotourism village can be achieved optimally. In addition, with this activity, the community can process their own cocoa fruit skin waste so that it can improve community welfare and income.